Dispersion оf Multi-Walled Carbon Nanotubes in Building Science оf Materials - B. M. Khroustalev; S. N. Leonovich; B. A. Yakimovich; G. I. Yakovlev; G. N. Pervushin; I. S. Polyanskikh; I. A. Pudov; D. R. Hazeev; A. V. Shaybadullina; A. F. Gordina; Mohamed Ali El Sayed; Ja. Keriene (Наука и техника)
The paper presents that modification of binding matrices with the help of dispersions of multi-walled carbon nanotubes (MWCNT) makes it possible to increase  physical and mechanical properties of building composites.